International Normalizing Ratio (INR) pada pasien multitrauma di RSUP Prof. Dr. R. D. Kandou Manado - Ratuwalangon, Verro; Kalesaran, Laurens T. B.; Panelewen, Jimmy; Sapan, Heber B. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Trauma is the leading cause of deaths in patients aged less than 45 years. Life-threatening bleeding which usually occurs in multitraumatic patients is caused by vascular injury along with coagulopathy. Several studies on multitraumatic patients showed that the risk of coagulopathy occurred along with increasing Injury Severity Score (ISS) which is directly proportional to the increase of International Normalizing Ratio (INR) with an impact of increase of mortality rate. Although INR as an indicator of coagulopathy in multitraumatic patients is still unclear, early monitoring of coagulation is important to detect coagulopathy due to trauma. This study aimed to obtain the relationship of INR and multi-traumatic patients. This was an analytical study with a cross sectional design conducted in Energency Room Prof. Dr. R. D. Kandou Hospital Manado from December 2015 to March 2016. ISS for multi trauma was Ëƒ16, meanwhile INR for coagulopathy risk was Ëƒ1.5 and without that risk was â‰¤1.5. There were 30 patients in this study aged 13-80 years old. Of 26 patients with ISS 17-25, one had INR >1.5. Moreover, ISS 26-59 was found in 4 patients; all had INR >1.5. All patients with INR Ëƒ1.5 died. Conclusion: Increase of ISS was proportionally to increase of INR which was further proportionally to the increase of mortality rate in multiraumatic patients.Keywords: coagulopathy, INR, ISSAbstrak: Trauma merupakan penyebab kematian utama pada pasein berusia kurang dari 45 tahun. Perdarahan yang mengancam nyawa pada pasien multitrauma biasanya disebabkan oleh cedera vaskular disertai koagulopati. Studi mengenai pasien multitrauma memperlihatkan adanya risiko koagulopati pada peningkatan nilai Injury Severity Score (ISS), yang secara proporsional sejalan dengan peningkatan nilai INR dengan akibat peningkatan angka kematian. Monitoring dini dari koagulasi sangat penting untuk mendeteksi terjadinya koagulopati akibat trauma. Walaupun demikian INR sebagai indikator koagulopati belum jelas. Penelitian ini bertujuan untuk menentukan hubungan INR dan pasien multitrauma agar dapat mengenali terjadinya koagulopati. Jenis penelitian ini analitik dengan desain potong lintang, dilaksanakan di Ruang Emergensi Bedah BLU RSUP Prof. R. D. Kandou Manado sejak Desember 2015 sampai dengan Maret 2016. Batasan multi trauma untuk ISS ialah skor Ëƒ16, sedangkan batasan untuk INR dengan risiko koagulopati Ëƒ1,5 dan yang tanpa risiko koagulopati â‰¤1,5. Hasil penelitian mendapatkan 30 pasien multi trauma berusia 13-80 tahun. Pada kelompok ISS 17-25 terdapat 26 pasien; satu diantaranya dengan INR >1,5. Pada kelompok ISS 26-59 terdapat 4 pasien; semuanya mempunyai INR >1,5. Semua pasien dengan INR Ëƒ1,5 meniggal. Simpulan: Peningkatan ISS proporsional dengan peningkatan INR yang selanjutnya proporsional terhadap peningkatan angka kematian pasien multitrauma.Keywords: koagulopati, INR, ISS